Effect of Adhesive Resin Application on the Durability of Adhesion to CAD/CAM Glass-Ceramics after either Hydrofluoric Acid Etching or Self-etch Primer Application - Vila-Nova, Taciana Emília Leite; Moura, Dayanne Monielle Duarte; de Araújo, Gabriela Monteiro; de Almeida Spinelli Pinto, Rafael; Leite, Fabíola Pessôa Pereira; Melo, Renata Marques [UNESP]; Özcan, Mutlu; e Souza, Rodrigo Othávio de Assunção (My University, 2022)
Purpose: To evaluate the effect of two surface conditioning methods, namely conventional hydrofluoric acid vs self-etching primer, and the application of adhesive on the bond strength of composite cement to CAD/CAM glass-ceramics. Materials and Methods: Blocks (N = 96) (12 x 10 x 2.5 mm) were manufactured, 24 for each tested ceramic type: lithium silicate ceramic (LS), polymer-infiltrated ceramic (PIC), leucite-reinforced feldspathic ceramic (FD), and lithiumdisilicate glass-ceramic (LD). For bond strength testing, 64 blocks were randomly divided into 16 groups (4 blocks per group) according to the following factors: ceramic: 4 levels; etching: 2 levels (HFS: hydrofluoric acid + silane or Monobond Etch & Prime [MEP]); and adhesive application: 2 levels, with (signified as A) and without. Then for each group, 15 composite cement cylinders (AllCem Dual, FGM) were built up. All specimens were subjected to thermocycling (10,000 cycles) and to shear bonding strength testing (SBS) (100 kgf, 0.5 mm/min). Mean shear stresses (MPa) were statistically analyzed by three-way ANOVA, Tukey’s test, and Weibull analysis. Results: The mean bond strength of group PIC-HFS-A (28.45 ± 7.6 MPa) was significantly higher than that of groups LS-HFS-A (12.11 ± 2.7 MPa) and FDHFSA (20.86 ± 2.0 MPa). Group PIC-HFS bond strength (25.02 ± 6.5 MPa) was significantly higher only when compared to group LS-HFS (15.82 ± 4.4 MPa). The LS group presented lower SBS compared to all other groups. No significant differences were found between HFS and MEP surface treatments. Conclusion: Surface treatment with MEP promotes adhesion similar to that of HFS. Additional application of adhesive after the surface treatments did not improve the bond strength.
Keywords: Adhesion; Bonding; Cad/cam; Dental ceramics; Dental materials.; Glass-ceramic; Shear bond; Treatment surface